Pengaruh Pemberian Aromaterapi Kayu Manis dengan Metode Inhalasi terhadap Intensitas Nyeri Dismenore pada Siswi di SMAN 1 Jogorogo Ngawi Jawa Timur - Dinda Egita Cahyani; Sri Handayani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Dysmenorrhea is pain during menstruation, caused by an imbalance of the hormones progesterone, prostaglandins, and stress or psychological factors. Although generally harmless, it can cause discomfort for women. Dysmenorrhea can be treated in various ways, one of which is with cinnamon aromatherapy which is one of the therapies of choice to treat dysmenorrhea in adolescent girls. Objective to determine the effect of cinnamon aromatherapy with inhalation method on dysmenorrhea pain intensity in female students at SMAN 1 Jogorogo Ngawi. This study used a pre-experimental design with a one group pretest-posttest design method with a total of 34 adolescent girls who experienced dysmenorrhea. The measuring instrument used NRS (Numeric Rating Scale) and data analysis using Wilcoxon Sign Rank test. The results of the study is the intensity of dysmenorrhea pain before being given cinnamon aromatherapy was dominated by moderate pain (85.3%) and the intensity of dysmenorrhea pain after being given cinnamon aromatherapy was dominated by mild pain (88,2%). The results of the Wilcoxon test showed a p value of 0.000 <0.05, meaning that Ho was rejected and Ha was accepted. There is an effect of cinnamon aromatherapy with inhalation method on dysmenorrhea pain intensity in female students at SMAN 1 Jogorogo.